The adoption of business intelligence systems in small and medium enterprises in the healthcare sector: A systematic literature review - Isyaku Salisu (Taylor & Francis Group, 2021)
In this era of industrial revolution (IR 4.0), coupled with the emergence of the deadly global pandemic of COVID-19, healthcare organizations are compelled to embrace new technologies for their routine decision-making. The Business Intelligence System (BIS) is one of the emphasized innovations, and due to its potential to provide more intellectual information for decision-making processes, has attracted the interest of industry analysts and policymakers. Literature suggests that the BIS is integrated by organizations in different sectors, but most BIS initiatives struggle to produce the anticipated outcomes. Moreover, the adoption of BIS in SMEs generally and healthcare specifically is rather insignificant. This is due to numerous factors. It is therefore necessary to discover and analyze the essential determinants affecting the adoption of BIS in healthcare SMEs. Therefore, this study tries to tackle this gap by exploring the relevant factors for BIS adoption using a systematic literature review (SLR) and an expert-ranking survey of 63 studies that were published in Scopus and WoS databases from 2011 to 2020. A total of 22 determinants are identified and sent to 15 experts. The data that were gathered from these experts were analyzed using SPSS. The results of the analysis indicated 15 determinants were significant, and one determinant was added by an expert. Consequently, a theoretical structure has been developed based on technology, organization, environment, and CEOs determinants and theories. The results of the current study will deepen the current BIS literature and advance the understanding of the significant elements of BIS adoption decision.